Effects of training based on the health belief model on Iranian women's performance about cervical screening: A systematic review and meta-analysis - Masoumeh Simbar; Masumeh Ghazanfarpour; Somayeh Abdolahian (Wolters Kluwer Medknow Publications, 2020)
CONTEXT: Pap smear test is one of the most important actions in preventing cervical cancer. This study aimed to perform a meta-analysis on all related literature about the effects of health belief model (HBM)-based training on Pap smear screening test performance of Iranian women. METHODS: The search was performed in Scopus, PubMed, and Web of Science. Eligibility criteria were limited to English and Persian language articles with experimental or semi-experimental methods until October 2019 that evaluated the effect of HBM-based training on Iranian women's performance of Pap smear test. We excluded studies that used both cervical and breast cancer screening together. RESULTS: Twelve studies were performed on totally 1605 participants. This meta-analysis showed that all of Health Belief Model (HBM) constructs improved significantly among HBM-based trained women, perceived susceptibility (standard mean division [SMD] =0.785; P = 0.002; confidence interval [CI] = 0.005 to 1.56; Heterogeneity; P = 0.013; I2= 97%)., perceived severity (SMD = 1.14; P = 0.001; CI = 0.66-1.62; heterogeneity; P < 0.001; I2= 92%), perceived benefits (SMD = 1.25; P = 0.001; CI = 0.545-0.135 heterogeneity; P = 0.003; I2= 97%), perceived barrier (SMD = 0.20; P = 0.001; CI = 0.44-1.24; heterogeneity; P < 0.001; I2= 92%) and perceived self-efficacy (SMD = 0.638; P < 0.001; CI =1.76-0.426; heterogeneity; P < 0.001; I2= 97%). CONCLUSION: Cervical screening education program based on the HBM can be effective on Iranian women's performance in their perceived susceptibility, perceived severity, perceived barrier, and perceived self-efficacy about Pap smear test.